2014
DOI: 10.1155/2014/689792
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Acetylcholine Receptor Antibody Test in Suspected Ocular Myasthenia Gravis

Abstract: Aim. To estimate the clinical significance of anti-acetylcholine receptor antibody (anti-AChR-Ab) levels in suspected ocular myasthenia gravis. Methods. In total, 144 patients complaining of fluctuating diplopia and ptosis were evaluated for serum levels of anti-acetylcholine receptor antibody and their medical charts were retrospectively reviewed. Subjects were classified into three groups: variable diplopia only, ptosis only, and both variable diplopia and ptosis. We investigated serum anti-AChR-Ab titer lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Looking at the pattern of diplopia, it can be seen that horizontal diplopia is more common than vertical diplopia, so there is more affected of horizontal extraocular muscle such as other reports in OMG. [11,12] Moreover, the 57.1% AchR Ab positivity rate was similar to that in previous reports (50%-60%). [4,13] Positive results group showed 2 more clinical ocular symptoms (both ptosis and diplopia), than the group with negative results.…”
Section: Discussionsupporting
confidence: 89%
“…Looking at the pattern of diplopia, it can be seen that horizontal diplopia is more common than vertical diplopia, so there is more affected of horizontal extraocular muscle such as other reports in OMG. [11,12] Moreover, the 57.1% AchR Ab positivity rate was similar to that in previous reports (50%-60%). [4,13] Positive results group showed 2 more clinical ocular symptoms (both ptosis and diplopia), than the group with negative results.…”
Section: Discussionsupporting
confidence: 89%
“…However, 80% of those diagnosed with OMG were AChR binding Abs seropositive. Conventionally, AChR-Abs testing is considered to have a low sensitivity for diagnosing OMG, with some studies suggesting approximately 44%-66% and other studies suggesting 14.1% (7)(8)(9). However, a recent, large observational cohort study demonstrated 70.9% sensitivity in AChR binding Abs testing (2).…”
Section: Discussionmentioning
confidence: 99%
“…However, 80% of those diagnosed with OMG were AChR binding Abs seropositive. Conventionally, AChR–Abs testing is considered to have a low sensitivity for diagnosing OMG, with some studies suggesting approximately 44%–66% and other studies suggesting 14.1% (7–9).…”
Section: Discussionmentioning
confidence: 99%
“…"Fluctuation, " the hallmark of the disease and its clinical signs, often impedes the diagnostic process. Moreover, serologic antibody testing, as well as repetitive nerve stimulation of peripheral muscles is reported to be less sensitive in OMG as compared to generalized myasthenia gravis (MG), with sensitivity rates of approximately 50% vs. up to 90% (6)(7)(8)(9)(10)(11)(12). Edrophonium testing may cause fatal adverse events and is often unavailable outside specialized institutions.…”
Section: Ocular Myasthenia Gravis -A Diagnostic Challengementioning
confidence: 99%